Technical Assistance In Preparing Sales And Purchase Deeds (Ajb) In Improving Students' Understanding Of Law In The Notary & Ppat Office Of Palu City - AZHAR SYARIF; ANDINI S TOMBOLOTUTU`; SELIN NATALIA RANDALONGI; RAHMATIA RAHMATIA; ZULFIKAR ZULFIKAR (Abdi Masyarakat, 2026)
Technical assistance in drafting sale and purchase deeds (AJB) provides a valuable learning opportunity for law students to grasp the legal procedures within a notary and land deed official (PPAT) office. This initiative is designed to deepen students’knowledge about the steps involved in drafting deeds, the necessary documention, and the legal consideration relevant to land sale and purchase activities. Approaches employed incude observing, engaging in practical exercises, and receiving mentorship from the notary and PPAT. The findings show that students acquaire hands-on experience throughout the deed preparation phases, which include reviewing documents, verifying information, and finalizing the deed with signatures. In addition, students come to appraciate the significance of precision and adherence to legal standards in the deed drafting process. Thus, this technical support effectively enhances the skills and readiness of law students as they preparw to enter the fields of notarial and land-related professions.